The Alcohol Policy Environment and Policy Subgroups as Predictors of Binge Drinking Measures Among US Adults. - Ziming Xuan; Blanchette, Jason; Nelson, Toben F.; Heeren, Timothy; Oussayef, Nadia; Naimi, Timothy S. (American Journal of Public Health, 2015)
Objectives. We examined the relationships of the state-level alcohol policy environment and policy subgroups with individual-level binge drinking measures. Methods. We used generalized estimating equations regression models to relate the alcohol policy environment based on data from 29 policies in US states from 2004 to 2009 to 3 binge drinking measures in adults from the 2005 to 2010 Behavioral Risk Factor Surveillance System surveys. Results. A 10 percentage point higher alcohol policy environment score, which reflected increased policy effectiveness and implementation, was associated with an 8% lower adjusted odds of binge drinking and binge drinking 5 or more times, and a 10% lower adjusted odds of consuming 10 or more drinks. Policies that targeted the general population rather than the underage population, alcohol consumption rather than impaired driving, and raising the price or reducing the availability of alcohol had the strongest independent associations with reduced binge drinking. Alcohol taxes and outlet density accounted for approximately half of the effect magnitude observed for all policies. Conclusions. A small number of policies that raised alcohol prices and reduced its availability appeared to affect binge drinking.